Experimental Strategy and Mechanistic View to Boost the Photocatalytic Activity of Cs3Bi2Br9 Lead‐Free Perovskite Derivative by g‐C3N4 Composite Engineering. (6th September 2021) - Romani, Lidia; Speltini, Andrea; Dibenedetto, Carlo Nazareno; Listorti, Andrea; Ambrosio, Francesco; Mosconi, Edoardo; Simbula, Angelica; Saba, Michele; Profumo, Antonella; Quadrelli, Paolo; De Angelis, Filippo; Malavasi, Lorenzo
Abstract: The rational design of heterojunctions based on metal halide perovskites (MHPs) is an effective route to create novel photocatalysts to run relevant solar‐driven reactions. In this work, an experimental and computational study on the synergic coupling between a lead‐free Cs3 Bi2 Br9 perovskite derivative and g‐C3 N4 is presented. A relevant boost of the hydrogen photogeneration by more than one order of magnitude is recorded when going from pure g‐C3 N4 to the Cs3 Bi2 Br9 /g‐C3 N4 system. Effective catalytic activity is also achieved in the degradation of the organic pollutant with methylene blue as a model molecule. Based upon complementary experimental outputs and advanced computational modeling, a rationale is provided to understand the heterojunction functionality as well as the trend of hydrogen production as a function of perovskite loading. This work adds further solid evidence for the possible application of MHPs in photocatalysis, which is emerging as an extremely appealing and promising field of application of these superior semiconductors. Abstract : A novel catalytic heterojunction made of Cs3 Bi2 Br9 and g‐C3 N4 is reported. The good band alignment between the two semiconductors provides the path to improve the carrier dynamics, and to promote a synergic effect resulting in improved photocatalytic hydrogen evolution and organic dye degradation reactions.